Cerebrovascular Reactivity Assays Collateral Function in Carotid Stenosis - Sobczyk, Olivia; Sam, Kevin; Mandell, Daniel M.; Crawley, Adrian P.; Venkatraghavan, Lakshmikumar; McKetton, Larissa; Poublanc, Julien; Duffin, James; Fisher, Joseph A.; Mikulis, David J. (Frontiers in Physiology, 2020)
In patients with carotid artery stenosis (CAS), the risk of stroke, its severity, and response to revascularization are strongly related to the availability of collateral blood flow. Unfortunately, there is poor agreement between observers in assessing collateral flow using flow-based imaging. We used changes in Blood-Oxygen-Level Dependent (BOLD) MRI as a surrogate of changes in regional cerebral blood flow in response to a hypercapnic stimulus (i.e., cerebrovascular reactivity, CVR) as indicating flow reserve ipsilateral to CAS. We hypothesized that some patients with hemodynamically significant CAS develop functional collateral flow as indicated by normalization of ipsilateral CVR. We identified 55 patients in our CVR database with various degrees of CAS assessed by angiography and classed them as < 50% stenosis, 50-69% stenosis, 70-90% stenosis, > 90% stenosis and full occlusion. CVR was measured as the change in BOLD signal in response to changes in end-tidal partial pressure of CO2 (Δ BOLD / Δ PETCO2) and normalized voxel-wise relative to the mean and standard deviation of the CVR in the corresponding voxels of an atlas of 44 healthy controls (CVR z scores). CVR and z scores were then averaged over gray matter (GM) and white matter (WM) on each side of the middle cerebral artery (MCA) territory. As hypothesized, CVR varied for each severity of CAS. Ipsilateral MCA territory CVR was less than normal in each class including that with < 50% stenosis (Student t-test, two-tailed; P=0.0014 for GM and P=0.030 for WM), with a trend of decreasing average CVR with increasing stenosis. Remarkably, the considerable individual variability in MCA CVR included some patients with normal CVR in each class–including that with complete occlusion. We conclude that in general CAS depresses downstream vascular reserve, but the extent of collateralization is highly variable and not predictable from the degree of stenosis, including both < 50% stenosis and complete occlusion. CVR may be the more reliable marker for recruitable collateral blood flow than degree of CAS.